Vertically-Ordered Mesoporous Silica Films for Electrochemical Detection of Hg(II) Ion in Pharmaceuticals and Soil Samples - Zhang, Mengqi; Zou, Yanqi; Zhou, Xiaoyu; Yan, Fei; Ding, Zhanling (Frontiers in Chemistry, 2022)
Rapid and simple determination of mercury ion (Hg2+) in pharmaceuticals and soil samples is vital for human health and the environmental monitoring. Vertically-ordered mesoporous silica films (VMSF) supported by the indium tin oxide (ITO) electrode surface were prepared by electrochemically assisted self-assembly method and utilized for electrochemical detection of Hg2+. Owing to the negatively charged channel walls and ultrasmall pore diameter, VMSF displays obvious cationic selectivity and has highly electrostatic interaction for Hg2+, giving rise to the strong electrochemical signals. By recording the anodic stripping signals of adsorbed Hg2+ using differential pulse voltammetry, quantitative detection of Hg2+ was achieved with a wide linear range (0.2 μM – 20 μM) and a low limit of detection (3 nM). Furthermore, considering the anti-fouling and anti-interference capacity of VMSF, the proposed VMSF/ITO sensor has been successfully applied to detect Hg2+ in pharmaceuticals and soil samples without tedious pretreatment processes of samples.